Antifungal activity of 2′-hydroxychalcone loaded in nanoemulsion against Paracoccidioides spp - Medina-Alarcón, Kaila P [UNESP]; Singulani, Junya De L. [UNESP]; Dutra, Luiz A.; Pitangui, Nayla De S. [UNESP]; Pereira-Da-Silva, Marcelo A.; Dos Santos, Mariana B. [UNESP]; Ayusso, Gabriela M. [UNESP]; Regasini, Luis O. [UNESP]; Soares, Christiane P. [UNESP]; Chorilli, Marlus [UNESP]; Mendes-Giannini, Maria J.S. [UNESP]; Fusco-Almeida, Ana M. [UNESP] (Taylor & Francis, 2020)
Aim: This study aimed to evaluate the activity of 2′-hydroxychalcone-loaded in nanoemulsion (NLS + 2′chalc), the cytotoxic effect and toxicity against Paracoccidioides brasiliensis and Paracoccidioides lutzii using a zebrafish model. Materials & methods: Preparation and physical-chemical characterization of nanoemulsion (NLS) and NLS + 2′chalc were performed. MIC and minimum fungicide concentration, cytotoxicity and toxicity were also evaluated in the Danio rerio model. Results: NLS + 2′chalc showed fungicidal activity against Paracoccidioides spp. without cytotoxicity in MRC5 and HepG2 lines. It also had high selectivity index values and no toxicity in the zebrafish model based on MIC values. Conclusion: NLS + 2′chalc is a potential new alternative treatment for paracoccidioidomycosis.
Keywords: antifungal; nanostructured lipid system; Paracoccidioides spp.; zebrafish model